Airbnb, or the (globalized) geopolitics of a contested tourist accommodation offer. From magnified disruption to generalized conflictualities... - Victor Piganiol (Via@)
The digital vacation rental platform Airbnb has established itself over recent years as one of the world leaders in tourist accommodation. Present in more than 100,000 cities across the globe, offering a selection of over seven million rentals via as many hosts who have become “partners” of the platform, it attracts millions of users. The multinational company has turned the travel industry upside down, to the point of being considered today as a player in its own right. Behind this phenomenal success, however, criticism from city stakeholders, angry residents, and other accommodation professionals has begun to emerge. Everywhere the platform is present, controversies and various problems have accumulated to the point of creating tensions that can cause conflicts. A geopolitical approach makes it possible to analyse Airbnb from a purely conflictual perspective by mobilizing the tools, concepts and reasoning invented by and for this field of geography, and to shed light on some of the forces that make the platform a “city disrupter”, particularly at the local and even micro-local levels, that of the space of the residence itself and its immediate environment.